The Role of Institutional Repositories (IRs) in Supporting Teaching, Learning and Research during Covid-19 in Kenyan Universities - Sang, Lucy Jelagat; Magut, Hellen Jepkemoi (University of Dar es Salaam Library Journal, 2023)
The abrupt closure of universities in 2020 because of COVID-19 forced many of them to adopt online learning through various technological platforms. Institutional repositories (IRs), digital archives of intellectual outputs of universities, could be important in online education. However, there is a dearth of empirical data on their ability to support teaching, learning and research in universities. This study aimed to investigate the role of IRs in supporting teaching, learning and research in Kenyan universities during the Covid-19 and to identify challenges faced by the universities in the usage of IRs. The study was informed by the technology acceptance model and adopted a mixed method approach and a multiple-case (embedded) research design. The study was conducted in four universities using a sample of 370 students, 322 academic staff and 12 key informants, selected by a mix of stratified, random, and purposive sampling technique respectively. The study found that IRs played crucial roles in supporting teaching, learning and research during the pandemic, with three out of every four respondents (n=424, 73%) using it for teaching, learning and research. Alarmingly, IR usage was lowest, Ï‡2 (4) = 73.462, p<0.0001, among the senior-most academic staff (professors, associate professors, and senior lecturers) relative to junior staff and students. Perceived lack of usefulness and difficulty of use of IRs constituted the major challenges. This study recommends the improvement of IRs perceived usefulness and perceived ease of use to enable them better support teaching, learning and research.